Praktik Pemakaian Hak Penamaan Pada Stasiun di Indonesia Ditinjau Dari Pemberian Lisensi Dalam HAKI - Muhamad Farudin (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
The practice of naming rights in Indonesia, particularly regarding the naming of stations by PT Kereta Api Indonesia (Persero), has become a significant phenomenon in marketing strategies and public facility management. This study aims to analyze the application of naming rights as a form of collaboration between companies and public transportation service providers and to evaluate its relevance within the context of intellectual property rights (IPR) law. Using a normative juridical research method, this study examines the regulations and challenges faced in implementing naming rights, including how trademark protection can enhance a company's image in the eyes of consumers. The findings reveal that naming rights not only increase brand exposure but also have the potential to become an additional source of revenue for public facility operators. However, the limited regulatory framework in Indonesia highlights the need for clearer guidelines to ensure transparency and alignment with societal values. This study provides recommendations for more optimal and regulation-compliant naming rights practices while emphasizing the importance of legal protection for trademarks in strengthening business identity in the era of modernization and globalization.